Variable-Strength Interaction for T-Way Test Generation Strategy - Syahrul A. C., Abdullah; Zainal H. C., Soh; Kamal Z., Zamli (Soft Computing Research Group,UTM Malaysia (SCRG Publication), 2013)
Often, t-way testing is usually adopted to trigger faults due to interactions. As a result, a myriad of useful t-way test generation strategies have been developed in order to generate t-way interaction test suite that is small in size while maintaining adequate t-way interaction coverage. Even though finding an efficient strategy to construct an optimal test suite is very valuable, another aspect to consider is the cost benefits of running the tests, i.e. at high level of interaction strength; the test suite size can become enormous. To balance the need for stronger interaction with the cost of running the tests, variable-strength interaction has been recommended. Hence, to enable support for construction of test suite with variable-strength interaction, a step by step procedure that extends our t-way test generation strategy, called Test Suite Generator (TSG) is highlighted. Benchmarking results against most existing strategies that support variable-strength interaction demonstrate that TSG is able to give competitive results.